Hubungan antara Body Shaming, Eating Disorder, Frekuensi Konsumsi Sumber Karbohidrat dengan Overnutrition pada Remaja Putri SMPIT Al-Mughni di Jakarta Selatan: Relationship between Body Shaming, Eating Disorder, Carbohydrate Consumption Frequency with Overnutrition in Adolescent Girls at SMPIT Al-Mughni in South Jakarta - Fadhilah, Devina Alifia; Permatasari, Tria Astika Endah (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2024)
Obesity or overweight (overnutrition) is a global epidemiological problem that poses a quite serious threat to world public health. Early adolescence, namely 10-15 years of age, is a vulnerable period for weight gain, characterized by critical changes in body composition, eating behavior, daily activities, and psychological adjustments. All changes in body shaming, eating disorders, and frequency of consumption of carbohydrate sources can be risk factors for overnutrition in young women. The aim of this research is to determine the description and relationship between body shaming, eating disorders, and the frequency of consumption of carbohydrate sources on overnutrition in young women at SMPIT Al-Mughni. This research uses quantitative methods with a cross sectional approach. The total sample was 44 respondents. The research results show that young women at SMPIT Al-Mughni have a BMI/U in the range of more than 36.4%. Adolescent girls who experience overnutrition in the high category of body shaming variable are 50% (p-value=0.039). Furthermore, the eating disorder variable in the binge risk category was 64.3% (p-value=0.009). The final variable, namely the frequency of consumption of carbohydrate sources in the >1 x/day category, was 37.8% (p-value=0.640). From the results of this study, it was concluded that overnutrition had a significant relationship with the variables body shaming and eating disorders, while it did not have a significant relationship with the frequency of consumption of carbohydrate sources.